Physical Activity and Functional Dependence in People with Arthritis: Insights from a Psychological Perspective - Goubran, Miriam (Université d'Ottawa / University of Ottawa, 2025)
Background: People with arthritis are less physically active than people without arthritis. Part of this difference may be explained by psychological factors, including attitudes toward physical activity as well as depression, and may affect functional independence. Objectives: This doctoral thesis aims to better understand the relationship between fear of movement, physical activity, pain, depression (depressive symptoms), and functional status in people with arthritis. Methods: First, a systematic review and a meta-analysis were conducted to assess the association between fear of movement and physical activity across several health conditions, including arthritis. Second, to examine the association between fear of movement and physical activity in people with arthritis, we assessed approach-avoidance tendencies towards physical activity in this population. Finally, data from the Canadian Longitudinal Study on Aging (CLSA) were analyzed to examine the potential mediating effects of depressive symptoms and physical activity on the relationship between pain and future functional dependence in people with arthritis. Results: The first article showed a negative correlation between fear of movement and physical activity in people with arthritis. The second article showed that approach-avoidance tendencies toward physical activity moderated the association between fear of movement and self-reported weekly engagement in physical activity. The third article showed that baseline pain was directly associated with future functional independence in basic (ADL) and instrumental activities of daily living (IADL), as well as indirectly related through effects on depressive symptoms and physical activity. Conclusions: This doctoral thesis highlights the importance of psychological processes for physical activity engagement in people with arthritis, suggesting that rehabilitation programs should go beyond pain management when aiming at improving functional status.
Keywords: Exercise; Health Status; Kinesiophobia; Pain; Psychology; Rehabilitation; Arthritis; Motivation; Mental Health; Depression; Physical Activity